Shell-and-tube reactor and high-temperature oxidation-reduction method
By using alumina-zirconia metal oxide mixture and optimizing surface finish and body structural characteristics, the problems of low reaction temperature management and heat exchange efficiency in high-temperature thermochemical reactions in the prior art are solved, and high efficiency and low cost are achieved Thermochemical reaction.
Patent Information
- Application Number
- CN202380038611.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-05
- Filing Date
- 2023-05-05
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively manage the reaction temperature and heat exchange efficiency when conducting thermochemical reactions at high temperatures, especially when using concentrated solar energy, resulting in low reaction efficiency and high cost.
Alumina-zirconia metal oxide mixture is used as the construction material for shell and tube reactors, and by optimizing surface finish and bulk structural characteristics, radiative heat exchange is maximized and heat loss is reduced.
A shell and tube reactor with efficient operation in the range of 600°C to 1800°C is realized, which improves heat exchange efficiency and energy utilization and reduces operating costs.
Smart Images

Figure CN119486986A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This patent application claims the priority of Italian Patent Application No. 102022000009257 filed on May 5, 2022, the entire disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to the realization of a shell and tube reactor (also called a shell and tube reactor) optimized to operate at high temperatures and to carry out thermochemical reactions occurring by absorption or heat transfer to transform raw materials into final products. In particular, the tube bundle reactor subject of the present invention is suitable for exchanging heat from a solar field (typically a concentrated solar field) with a reagent system capable of carrying out a chemical transformation process using renewable energy. The reagent system is formed by a collection of substances capable of reacting at temperatures above 600° C., either alone or in the presence of other substances and / or solid systems (catalytic or non-catalytic). Background Art
[0004] The main limiting factor of thermochemical reactions is the efficiency of the heat exchange between the energy source and the reagent system. The higher the exchange efficiency between the heat transfer fluid and the reagent system, the better the reaction effect. Since some thermochemical reactions mainly occur in the high temperature range (for example, above 600°C), improving the efficiency of the heat exchange between the heat source and the reagent system means that it is necessary to develop a technical solution that allows maximizing the heat exchange. A practical example of a high-temperature thermochemical reaction is a reaction in which the heat source is represented by a heat transfer fluid heated by solar energy with the aid of a concentrated solar power plant. The technical capabilities that make high-temperature thermochemical reactions possible allow the use of new renewable energy sources, such as, for example, concentrated solar power plants. The use of renewable energy also makes it possible to reduce or eliminate greenhouse gas emissions compared to the use of energy from fossil energy sources. One of the most studied renewable energy sources in this field is solar energy through the use of concentrated solar technology.
[0005] Concentrated solar power (CSP) technology allows to concentrate the solar radiation impinging on a highly reflective surface in a predefined area (receiver). In this way, a high flow of solar energy is available in the receiver, with the possibility of producing high temperatures (up to 2000°C). This solar thermal energy can be used for various purposes, such as for the generation of electrical energy. One of the most studied uses of concentrated solar energy is for promoting endothermic reactions, i.e. reactions that require external heat to occur. To this end, two main methods are known: 1) direct heating of the reagents by exposing them to a stream of reflected and concentrated solar rays, so that the desired reaction occurs directly in the receiver (direct solar reaction), 2) using the receiver to heat a fluid (called a heat transfer fluid), which in turn heats the reagent system in the appropriate area and mode (indirect solar reaction). The advantage of indirect solar reactions is that by regulating the flow of the heat transfer fluid (usually in the gas phase, taking into account the temperatures involved), the reaction temperature can be better managed to maximize the yield and it is possible to use part of the heat of the receiver to implement heat storage. Thermal storage (TES) allows thermal resources to be available when solar heat does not exist or is unavailable (e.g., at night or under weather conditions that are not conducive to sunlight). In this way, continuous heat flow can be ensured, allowing thermochemical processes to operate continuously for more than 24 hours, thereby avoiding shutdowns and restarts that reduce energy efficiency and hourly productivity. The scheme using indirect solar reactions requires the development of dedicated reactors, in which heat transfer fluids effectively exchange heat with reagent systems and allow reagents to be in optimal conditions to synthesize desired products. The first system, i.e., a directly heated reactor, has limitations in its development: unless a large reactor is used, the amount of reagent materials that can reach the desired temperature is limited by the surface of the reactor itself. In the past few years, many solar reactors (both direct and indirect) have been proposed and developed (see, for example, Energies, 11, 2358, 2018; doi: 10.3390 / en11092358).
[0006] Most direct solar reactors are actually an integral part of the receiver, which has the following major problems.
[0007] There are inherent difficulties in controlling the reaction temperature. The efficacy of the solar field is derived from natural sunlight, so the temperature is higher at about noon of the day and lower at sunrise and sunset. Maintaining a constant reaction temperature (a normal requirement in order to have a constant product yield, thereby avoiding conversion rate variations that increase the downstream processing system) becomes difficult to achieve, where any energy supply from non-solar energy sources is required at some times or cooling is required at other times. In addition, direct solar heating can cause uneven heating of the reagent material, and there may be a temperature gradient between the irradiated portion and the underlying layer, which is a phenomenon that is exacerbated when implementing oxidation reactions that are exothermic in nature. The surface portion of the reagent material that reacts first will heat more than the underlying portion that has not yet participated in the reaction.
[0008] Managing the energy flow from the solar source is also complicated, making it less efficient in carrying out the reaction continuously for more than 24 hours. Using solar energy for possible storage would involve, in addition to the reactor, a second receiver or a heat exchanger with the fluid, which would increase operations and costs even more.
[0009] In the case of direct solar reactions, the reactor-receiver must be located at the point of concentration of the sun's rays. In tower concentration farms, this involves installing and managing a complex system at the top of the solar tower, which creates problems due to its height and the reduced available space. If the CSP (concentrated solar power) farm is formed by parabolic dish solar concentrators, the reactive system is no longer unique, but multiplied by the number of concentrator systems, which increases the cost of the solar farm due to the need to move reagents and products in a considerable number of reactors.
[0010] The approach of indirect solar reaction means that the solar field concentrates energy in the receiver by heating the heat transfer fluid with high efficiency. This heat transfer fluid can be sent partly to the reactor (where thermochemical synthesis occurs) and partly to the heat storage system or other system to enhance its energy content (for example, to generate useful electrical energy in the process unit, and the solar reactor in the process unit is a component such as a pump, a compressor, a controller, a recovery system, etc.). Due to the loss of the transmission pipeline along the heat transfer fluid and the non-quantitative heat transfer yield between the various components, the overall thermal efficiency of the process is minimally reduced. However, the technology based on indirect solar reaction allows continuous operation, with more operating options and greater flexibility. For example, it is no longer necessary to use a reactor with a quartz window for passing the sun's rays (these windows usually reduce firmness, and therefore reduce safety in working at temperature and pressure) or a reactor with a higher surface / volume cavity (where the sun's rays are concentrated). The reactor used for indirect solar reaction allows better control of the temperature at which the reaction occurs, thereby optimizing the yield, and therefore avoiding all the problems listed above about direct heating.
[0011] As an effective technology, the prior art proposes the use of reactors heated by solar energy through high temperature (HTF) heat transfer fluids. One of the most easily used heat transfer fluids (HTF) is water or a mixture of water and CO2, which allows high thermal efficiency because it has a high ability to absorb energy both by direct irradiation and by radiation.
[0012] An application of particular interest (which utilizes CSP technology with indirect solar reactions) is the production of methanol as solar fuel from methane / carbon dioxide / water, or hydrogen from water / methane. One of the main contributions to the greenhouse effect comes from carbon dioxide, and its significant increase in the atmosphere is the subject of action and goals at the international level. In an attempt to manage and minimize the production of CO2 from anthropogenic activities, in recent years, attempts have been made to utilize the same carbon dioxide where it is produced, avoiding sudden combustion, for example in oil fields. In recent years, many efforts have been made to develop processes for converting CO2 into other products or into energy carriers (for example, into methanol for use in motor vehicles or as a solvent or reagent). It should be remembered that methanol has a higher octane number, is easier to burn and has a higher latent heat of vaporization than gasoline. For these reasons, greater energy efficiency of engines and a reduction in gaseous emissions (HC, NOx) can be obtained by using methanol. Unfortunately, the high thermodynamic stability of carbon dioxide requires high energy to be able to convert it into other products. Chemical conversion to synthesis gas (a mixture of CO and H2) is one of the most studied ways to be able to produce methanol. Industrially, synthesis gas is mainly synthesized from fossil sources of natural gas or coal via steam reforming, combined steam reforming, catalytic and non-catalytic partial oxidation. In order to be able to produce synthesis gas from carbon dioxide, it is important to have abundant and cheap energy available in order to implement the endothermic reaction of CO2 valorization. Considering its renewable characteristics, concentrated solar power generation becomes a preferred option. From this point of view, a route is being developed for the thermochemical conversion of carbon dioxide and water based on metal oxides MO, which performs a two-stage redox cycle as shown in the following diagram:
[0013] Reduction: MOox→MOred+O2 (endothermic)
[0014] Oxidation: MOred+CO2→MOox+CO (exothermic)
[0015] MOred+H2O→MOox+H2(exothermic)
[0016] The redox cycle of oxides is formed by the following processes:
[0017] Thermal reduction of metal oxides at high temperatures with the release of oxygen;
[0018] The reduced metal is oxidized by carbon dioxide and water at a relatively low temperature, resulting in the production of synthesis gas.
[0019] In this way, by continuously carrying out reduction and oxidation cycles, synthesis gas can be produced for application purposes.
[0020] In order to be able to utilize the solar heat contained in the HTF, it must be exchanged with the substance to be heated inside the reactor. Such a reactor should conceptually allow:
[0021] a) The HTF fluid heats the reagent material, such as cerium oxide (referred to as ceria), to warm it and maintain it at the reaction temperature, thereby performing this action continuously over time;
[0022] b) contain the heated redox material, reacting it with a continuous flow of reducing and oxidizing substances, remaining intact both for the effects of temperature and pressure (using gases, and the use of gases under pressure certainly optimizes the process since it allows reducing the volumes involved and overcoming any pressure losses in the distribution and connecting pipes) and for the reagents and products of the synthesis reaction (CO, H2, CO2, O2, H2O, CH4) under the operating conditions used;
[0023] c) efficient heat exchange between HTF heat transfer fluid and reagent materials to maximize production yield and energy efficiency;
[0024] d) Minimize heat losses due to radiation and conduction.
[0025] The ideal configuration for a reactor based on an indirect solar reaction comprises a shell in which a heat transfer fluid (HTF) flows and a tube bundle in which the desired thermochemical reaction takes place.
[0026] When the design temperature is below 700° C., according to the teachings of the prior art, special metal alloys (e.g., Inconel 601) can be used to construct the tube bundle reactor in order to maintain sufficient resistance characteristics of the material when the temperature rises. When the design temperature of the tube bundle reactor exceeds 700° C., problems related to high temperatures and degradation of the mechanical properties of the construction materials make it extremely difficult (almost impossible) to design a tube bundle reactor, as the design temperature approaches 1500° C. In fact, the prior art is not satisfactory in terms of the teachings related to realizing tube bundle heat exchange devices at temperatures above 700° C., especially when the reagents and reaction products include substances with oxidation activity such as, for example, water or oxygen.
[0027] When the design temperature exceeds 700° C., it is known to use ceramic materials which have inherent properties that enable them to better withstand exposure to extremely high temperatures. Two major categories of ceramic materials can be distinguished: oxide-based ceramic materials and non-oxide-based ceramic materials. The first category includes aluminum oxide and zirconium oxide, the second category includes silicon carbide (SiC). In the case of having to operate at high temperatures (for example, temperatures above 700° C.) while in the presence of fluids with oxidative activity, the use of special steels, Ni, Cr and Mo-based alloys must be excluded (in addition to temperature resistance, they will be oxidized in a short / medium period of time, thus showing structural problems); moreover, many ceramic materials must be avoided, especially non-oxide-based ceramics (such as SiC), which are compatible with high temperatures but not resistant to oxidants, especially in terms of "environmental corrosion cracking" or even showing sublimation phenomena. In addition, since the tube bundle reactor has the function of obtaining the maximum heat exchange efficiency between the heat transfer fluid (HTF) and the fluid inside the tube bundle, some ceramic materials are not very suitable for heat exchange. Ceramic materials known per se for use at temperatures above 700° C. include alumina (aluminum oxide Al 2 O 3 ) and zirconium oxide (zirconium dioxide ZrO 2 ).
[0028] Alumina resists oxidation but has a low thermal conductivity, which promotes its use to limit heat dissipation but reduces in principle the possibility of using it for applications in which maximizing heat exchange is an essential requirement; in fact, as we will see later, the contribution of convection, conduction and radiation to the heat exchange mechanisms depends on the temperatures involved, and above temperatures of about 600° C., heat transfer by radiation prevails over that by conduction. Therefore, the low thermal conductivity of alumina is no longer a limiting factor for the efficiency of heat exchange at temperatures exceeding 700° C. Alumina is, however, relatively brittle, exhibits a moderate resistance to fracture and therefore tends to form cracks that may cause structural damage to the reactor.
[0029] Silicon carbide (SiC) does not have the limitation of moderate heat transfer through the inherent conduction of alumina. This type of material may seem suitable for the realization of tube bundle reactors. However, considering the realization of high temperature shell and tube reactors for processing fluids containing oxidants, silicon carbide exhibits microporosity, which makes it unsuitable for safely containing oxidizing fluids that may leak, especially under conditions of pressure higher than ambient pressure. In addition, although it is usually specified as resistant to oxidants, the microporosity effects reported in the literature show that the resistance of SiC to oxidants is only effective for short time periods, and is not effective for long-term contacts (such as those necessary in continuous thermochemical processes, such as those of indirect solar radiation reactors). (See Ceramics International 42 (2016) 1916-1925, http: / / dx.doi.org / 10.1016 / j.ceramint.2015.09.161 and Ceramics International 42 (2016) 4679-4689; http: / / dx.doi.org / 10.1016 / j.ceramint.2015.11.117.) In addition, sublimation, pitting, and environmental corrosion cracking effects may occur in SiC, especially at temperatures greater than 700°C, making it unsuitable for use in high-temperature tube bundle reactors. Summary of the invention
[0030] The object of the present invention is to realize a tube bundle reactor which overcomes the drawbacks of the prior art and allows operation at very high temperatures ranging from 600° C. to 1800° C., even in the presence of an oxidant circulating inside the reactor. In particular, the reactor subject of the present invention is particularly suitable for use in concentrated solar energy installations based on indirect solar radiation technology. In this type of installation, in fact, the heat transfer fluid (HTF) is heated by means of concentrated solar radiation and represents a heat carrier that releases heat in the reactor to promote the thermochemical reactions inside the shell and tube reactor.
[0031] The invention also relates to a redox method at high temperatures ranging from 600°C to 1800°C.
[0032] In the context of the present invention, pressure values are measured in barg (a unit of measurement representing the difference between the pressure in a space (bar) and the atmospheric pressure (bar)).
[0033] In the context of the present invention, mixtures of metal oxides are intended to mean mixtures containing only alumina and zirconia as well as mixtures comprising alumina, zirconia and other elements, in particular alumina-zirconia metal oxide mixtures toughened with yttria or magnesia.
[0034] According to the present invention, a tube bundle reactor has been realized, the construction material of which is a mixture of alumina-zirconia metal oxides. As is customary in the art, the construction material of a shell and tube reactor refers to the material from which at least the main parts of the reactor (i.e., the shell and tube reactor) are made. The use of this material makes it possible to combine the advantages of alumina and zirconia in order to ensure that the reactor has sufficient mechanical resistance at temperatures between 600° C. and 1800° C., as well as good resistance to the action of oxidants during continuous operation. Therefore, the shell and tube reactor according to the present invention is based on the use of a mixture of metal oxides (alumina / zirconia), which is preferably toughened with yttria or magnesium oxide according to known techniques, thereby allowing the characteristics of the individual components to be utilized while minimizing their defects. Zirconia is added to alumina to produce a material called zirconium oxide toughened alumina (ZTA), which, together with toughening with yttria or magnesium oxide, greatly reduces the brittleness of the material and is suitable for processing into the desired form. This type of ZTA composite material, due to its low conductivity, makes it possible to contain heat inside the reactor, thereby reducing energy losses to the outside. The reactor of the invention is also characterized by a specific surface finish for the heat exchange surfaces in order to maximize the radiation component of heat transfer that dominates when the temperature rises in the range of 600°C to 1800°C (for example, at a temperature of 1000°C, the heat transfer by radiation in the ZTA material is about 10 times higher than the heat transfer by conduction). As described below, the specific characterization of the bulk components (material matrix) of the mixture of metal oxides, i.e. the definition of the porosity, grain size and pore diameter (or pore diameter) of the ZTA material matrix, also helps to improve the heat exchange and thus minimize heat losses when necessary. The discovery of this possibility is based on laboratory experiments carried out on specific samples of alumina-zirconia (ZTA) materials, which were properly treated and characterized, as well as modeling studies of heat exchange.
[0035] The present invention also relates to a high temperature redox process in the presence of an oxidizing agent as described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Features and advantages of the present invention will become apparent from the following description of non-limiting embodiments of the invention with reference to the figures of the accompanying drawings, in which:
[0037] - Figure 1 is a simplified view of a shell and tube reactor with some components removed for clarity;
[0038] - Figure 2 is a graph showing the relationship between diffuse reflectance and wavelength in the results of tests conducted on sintered alumina-zirconia (ZTA) (having the same surface treatment);
[0039] - Figure 3is a graph showing the relationship between diffuse reflectance and wavelength in the results of tests conducted on sintered alumina-zirconia (ZTA) as the surface finish and grain size of the substrate vary;
[0040] - Figure 4 is a graph showing the relationship between emissivity and temperature in the results of tests performed on sintered alumina-zirconia (ZTA) of varying surface finish;
[0041] - Figure 5 is a graph showing the evolution of the emissivity of various types of materials as a function of temperature;
[0042] - Figure 6 A simplified view showing an infinitely long cylinder with some characteristic dimensions;
[0043] - Figure 7 is a graph showing the trend of the absorption coefficient of superheated water vapor at 1200 K and 10 bar with respect to wavelength. DETAILED DESCRIPTION
[0044] In order to fully demonstrate the main points of the invention, it is necessary to define how the heat transfer mechanisms occur between two objects, with particular attention paid to the radiation component. It is known that heat transfer between two objects occurs by conduction, convection and radiation. Each material is characterized by its specific ability to exchange heat by these mechanisms, taking into account the geometries and temperatures involved. However, it is important to remember that as the temperature increases, the incidence of heat transfer mechanisms by conduction and convection decreases sharply, in favor of the heat exchange component by radiation. At temperatures above 600°C, the heat exchange component by radiation becomes dominant, thereby determining the design rules for efficient exchange systems (see Thermal Radiation Heat Transfer, John R. Howell, M. Pinar Kyle Daun and Robert Siegel). For these reasons, we will analyze in more detail the mechanisms of heat transfer via radiation at high temperatures, specifically defining how the surface and “bulk” of a material (the matrix of the material itself) contribute to radiative heat exchange.
[0045] The transfer of energy through radiation can be described by the equations for the interaction of electromagnetic waves with materials. When an electromagnetic wave interacts with a surface between two different media, from the law of conservation of energy we obtain:
[0046] ρ r +ρ d +α+τ r +τ d =1
[0047] in:
[0048] ·τ r is the direct transmittance
[0049] ·ρ r is the direct reflectivity or specular reflectivity
[0050] ·τ d is the diffuse transmittance
[0051] ·ρ d is the diffuse reflectivity
[0052] α is the absorbance or linear absorption coefficient
[0053] Diffuse reflectivity ρ d Defined by the ratio of the incident energy from the first medium to the energy dispersed in the half-plane of the first medium, integrated over the solid angle 2π (hemisphere of the first medium).
[0054] Diffuse transmittance τ d Defined by the ratio of the incident energy from the first medium to the energy dispersed in the half-plane of the second medium, integrated over the solid angle 2π (the hemisphere of the second medium) after crossing the surface between the two media.
[0055] The sum σ s =ρ d +τ d Defined as the surface scattering factor, where surface scattering phenomena are considered as any deviation of the propagation direction from the direction defined by Snell's law.
[0056] The total surface reflectivity is equal to the sum of the direct reflectivity and diffuse reflectivity components ρ = ρ d +ρ r , and the total surface transmittance is equal to the sum of the diffuse transmittance and direct transmittance components τ = τ d +τ r . Therefore, the energy balance relationship can sometimes be summarized as:
[0057] ρ+α+τ=1
[0058] As mentioned above, the properties of the material matrix ("bulk") also contribute to the radiative transfer of heat; in fact, in addition to the surface properties of the surface between the first and second medium, there are also some properties, typically "bulk", which define the behavior of the second medium in terms of absorption and scattering by means of the coefficients α (linear absorption or absorbance coefficient) and σ (linear scattering coefficient), which should not be confused with the surface scattering coefficient σ relative to the sum of the diffuse transmittance and reflectance of the surface. sThe sum of the linear scattering coefficient and the linear absorption coefficient is defined as the linear attenuation coefficient κ, which conforms to the Lambert-Beer's law:
[0059]
[0060] in
[0061] κ=α+σ
[0062] The distance l = 5 / (α+σ) is defined as the penetration depth into the second medium; if the thickness of the second medium exceeds this value, the medium can be considered substantially opaque, with an attenuation greater than 99%.
[0063] The emissivity ∈ is equal to the ratio between the energy emitted as thermal radiation of a wavelength defined by the surface temperature of the medium (according to Stefan-Boltzmann and Planck's law) and the corresponding similar energy emitted by a black body placed at the same surface temperature. A black body is an idealized object that absorbs the entire incident electromagnetic radiation, regardless of its wavelength and the angle of incidence. It must be emphasized that a "black body" emits radiation (contrary to what its name might suggest), but the wavelength it emits is well defined by its temperature, while it absorbs radiation of any wavelength that impinges on its surface. Furthermore, a black body is a "perfect diffuser" in that the emitted radiation is irradiated isotropically.
[0064] The behavior described here also manifests itself when radiation passes through a gas, a medium in which scattering, absorption, etc. occurs, which is defined as a "participating medium." If the behavior of the gas in the medium does not depend on the wavelength of the radiation, it is called a "grey gas" model.
[0065] In general, the behavior of radiation in transit from a first medium with a refractive index n1 into a second inhomogeneous medium with a refractive index n2 depends not only on the nature of the separation surface between the two media, but also on the "bulk" properties of the second medium; indeed, if the radiation transmitted in the second medium is further reflected / refracted and / or undergoes scattering within the second medium itself, these effects have an impact on the first medium. These effects manifest themselves when the second medium has the properties of a translucent medium (i.e. a medium that partially allows the passage of radiation), but they are greatly simplified if, on the contrary, it can be considered "opaque", i.e. where τ = 0 when the energy balance relation simplifies to ρ + α = 1. In fact, according to Kirchoff's law ∈ = α, and therefore the energy balance can also be written as ∈ = 1 - ρ.
[0066] With the above disclosure in mind, we now look at how "bulk" radiation effects (i.e., associated with the matrix of the material) contribute to heat transfer via radiation as grain and pore size and porosity vary.
[0067] In porous media such as alumina-zirconia oxide (ZTA) mixtures, linear scattering is related to the particle size of the material particles and the size of the pores. The material particles start from submicron size up to micron size. Since the radiation involves phenomena related to the temperature range of 700-1500 ° C and about the micron scale (2.5÷1.5μm), the linear scattering phenomenon can only be partially modeled as Rayleigh scattering; a more accurate modeling can be obtained through Mie scattering.
[0068] As expected, the linear scattering coefficient σ and the linear absorption coefficient α help determine the linear attenuation coefficient κ. A radiative conductivity Λ can be defined as rad (See "Thermal radiation heat transfer" - Howell, Siegel, Menguc), which is exactly the same as the radiation conductivity defined in Fourier's law of heat transmission, which is equal to:
[0069]
[0070] Here σBoltz denotes the Boltzmann constant, which leads to a strong advantage in heat transfer by radiation due to the increase in temperature and also due to the decrease in the linear attenuation coefficient κ.
[0071] The trend of the κ value can be inferred using the Kubelka-Munk's theory of diffuse reflectance, complemented by an evaluation of Mie scattering.
[0072] In a semi-transparent medium such as alumina-zirconia (ZTA), in which part of the radiation penetrates the interface surface between the media to a depth equal to l=5 / (α+σ), the coefficient κ decreases, thereby increasing the depth of radiation penetration as a function of:
[0073] a) Increase in ceramic particle size;
[0074] b) reduction of porosity;
[0075] c) Increase in pore size.
[0076] In an optically often medium, the relationship between the linear absorption coefficient and the linear scattering coefficient is determined by the following relationship:
[0077]
[0078] where ρ d is the diffuse reflectivity of the medium.
[0079] For ρ close to 1 d , as can be found in the tested alumina-zirconia (ZTA) samples, the share of the linear scattering coefficient relative to the linear absorption coefficient (both together constitute the linear attenuation coefficient) dominates and depends on the pore and particle size and the porosity.
[0080] Since the linear absorption coefficient α is related to the linear attenuation coefficient κ and is consistent with the emissivity of the medium according to Kirchhoff's law, it follows that, in terms of the bulk properties of the ZTA, the emissivity ∈ follows the same trend as the linear attenuation of the medium due to scattering.
[0081]
[0082] Table 1 - Relationship between radiation characteristics and bulk properties in ZTA
[0083] As summarized in Table 1 above, for the alumina-zirconia (ZTA) materials, it can be noted how the properties of the material matrix ("bulk") affect the radiation properties of the material itself; in particular, an increase in the average diameter of the grains and / or the average diameter of the pores results in a decrease in the emissivity and linear attenuation coefficient. A decrease in the porosity of the material also contributes to a decrease in the emissivity and linear attenuation coefficient.
[0084] These trends have been experimentally verified on sintered alumina-zirconia (ZTA) samples.
[0085] In particular, two types of alumina-zirconia 80 / 20 (ZTA) were tested, in which the powder was treated with a 0.176 μm sieve before sintering. The first type of alumina-zirconia (ZTA) was obtained by sintering the powder that passed through the sieve, while the second type was obtained by sintering the powder that remained on the sieve.
[0086] Figure 2Reported are graphs of diffuse reflectance versus wavelength, obtained from laboratory measurements carried out using a spectrophotometer equipped with the accessories described in standard ASTM E 1331. Based on the results of these measurements carried out on sintered alumina-zirconia (ZTA) obtained by isostatic pressing, it can be noted that, in the ZTA tested, the diffuse reflectance (with the same surface treatment) increases with the fineness of the grains, due to an increase in bulk scattering phenomena.
[0087] Therefore, the share of the ZTA emissivity associated with bulk scattering also increases.
[0088] Now let us see how surface radiation effects contribute to heat transfer via radiation as the surface finish varies.
[0089] In the literature (reference "Thermal radiation heat transfer" - Howell, Siegel, Menguc), it is known from the Drude and Davis theory for conducting media that when the ratio between the radiation wavelength λ and the roughness (expressed by its roughness parameter Γ) is such that When the wavelength rises above 5 times the roughness, the emissivity of the medium surface increases. In fact, when the wavelength rises above 5 times the roughness, the surface has almost complete specular reflection and very little surface scattering. Since the emissivity in an opaque metal medium is equal to ∈=1-ρ, if the surface exhibits strong specular reflection characteristics, the emissivity tends to 0. On the other hand, if the wavelength is lower than the roughness value, there is almost only surface scattering in the radiation propagation domain within the ray tracing range, then the Snell reflection tends to cancel, and therefore the emissivity increases, resulting in a value close to 1. (Refer to "Modeling the effects of surface roughness on the emissivity of aluminum alloys", Chang-Da Wen, Issam Mudawar, "International Journal of Heat and Mass Transfer", 2006). In the context of the present invention, the surface roughness values described below refer to (even if not explicitly stated) the roughness standard Ra according to the average knowledge of those skilled in the art; the roughness value according to the roughness Ra is defined as the arithmetic mean of the deviations (in absolute value) of the actual profile of the surface from the average line. The reference to surface roughness values according to the roughness standard Ra represents a conventional method of defining surface roughness according to common knowledge (when roughness is indicated without further clarification, it is in fact usually understood as roughness Ra). In addition, surface roughness values measured according to the Ra standard are also evident in the previously cited document "Modeling the effects of surface roughness on the emissivity of aluminum alloys", Chang-Da Wen, Issam Mudawar, "International Journal of Heat and Mass Transfer", 2006.
[0090] Similar considerations for porous and especially not completely opaque but semi-transparent dielectric media such as ZTA metal oxide mixtures, in which the penetration depth of radiation in the medium reaches values of several millimeters, are not available in the literature.
[0091] For this purpose, samples of alumina-zirconia (ZTA) material with different surface finishes were therefore produced in order to analyze whether the emissivity characteristics could be influenced with the variation of the surface treatment of the material, which in turn could depend on the roughness. The results of this experiment are very useful for defining the surface treatment characteristics of the various components of the tube bundle reactor that is the subject of the present invention.
[0092] Two sample series of 80 / 20 alumina-zirconia (ZTA) material were then prepared, the first having a ground (polished) surface (roughness 0.1 μm) and the second having a surface treated with FEPA 180 abrasive grade "virgin" paper before sintering (thus enabling a surface roughness of about 80 μm (rough) to be produced). It should be recalled that, according to the Planck relationship, the radiation mainly involved in phenomena in the range 700-1500° C. is of the order of micrometers (2.5÷1.5 μm).
[0093] It is important to point out that, as we have seen above, the diffuse reflectance due to bulk scattering phenomena is directly related to the emissivity, since it is in turn related to the absorbance α through the linear attenuation coefficient κ and, according to Kirchhoff's laws, to the emissivity ∈. Conversely, in the case of the diffuse reflectance related to the surface finish, the diffuse reflectance increases when the specular reflection decreases and therefore when the roughness increases. It is therefore reasonable to expect that, as happens with metals (according to the literature), the diffuse reflectance and therefore the emissivity will increase with increasing roughness.
[0094] For alumina-zirconia metal oxide (ZTA) mixtures, this expected trend is reflected by Figure 3 The experimental results shown in confirm that for the ground (polished) surface, the diffuse reflectivity is lower and also confirm that Figure 2 Regarding the trend of grain size, the overall results of diffuse reflectance are attributed to the overlap of bulk and surface effects.
[0095] In summary, in order to confirm that the results obtained for diffuse reflectivity can be converted to emissivity ∈, a useful parameter for characterizing reactor-specific heat transfer properties, emissivity measurements were performed on ZTA material samples at temperatures between 900 and 1200 °C using a thermal imaging camera. The results of these measurements are reported in Figure 4 This confirms the conclusion that the emissivity increases in the presence of surface roughness above the wavelength scale involved, even for semi-transparent dielectric ceramic materials such as alumina-zirconia (ZTA), and is consistent with Figure 5 This is consistent with the theoretical expectation for aluminum oxide.
[0096] Summarizing the above, Table 2 shows the contribution to the overall radiation effect of different "bulk" and surface (roughness) parameters of alumina-zirconia (ZTA).
[0097]
[0098] Table 2 - Relationship between overall radiation characteristics and material properties and surface treatment
[0099] Previously, a relationship has been reported that identifies the conductivity of radiation equivalent to that of a medium expressed as a bulk property as a linear attenuation coefficient, κ.
[0100] The radiation properties of the medium which can be used to realize the tube bundle reactor according to the invention have yet to be determined and depend on the surface treatment of the walls on the shell side and on the tube side.
[0101] A relationship is known in the literature ("Heat and mass transfer fundamentals and applications" - Yunus A. Cengel, Afshin J. Ghajar) which allows determining the properties of heat transfer by radiation between two surfaces or between a surface and a medium, which is defined as a "participant" in the theory of heat transfer by radiation, i.e. a medium such as a gas that proves to be active in terms of radiation emission (with a tendency proportional to the fourth power of the temperature) at the operating temperature according to the Stefan-Boltzmann law, and which exhibits a linear attenuation coefficient for the radiation that satisfies the Lambert-Beer law.
[0102] These relations are obtained by solving the radiative transfer equation (RTE) problem in terms of J radiance, which allows the heat transfer to be managed by equivalent to a "grid":
[0103]
[0104] Where E b and J d acts as a potential, and It acts as the surface radiation resistance.
[0105] By combining this equation with the equation for the surface relative to another medium or "participating media" (such as a gas), the effect of heat transfer by radiation and the overall resistance between the two media is obtained.
[0106] In an infinitely long cylinder (such as Figure 6 In the case of a cylinder), since some parts of the reactor can be modeled in a first-order approximation, the relationship between the radiation resistance of the inner cylinder and the outer cylinder is determined as follows:
[0107]
[0108] in:
[0109] ·R 1→2 Is radiation resistance
[0110] r1 is the radius of the inner cylinder
[0111] r2 is the radius of the outer cylinder
[0112] ∈1 is the emissivity of the inner cylinder
[0113] ∈2 is the emissivity of the outer cylinder
[0114] In the case of equal radius, that is, directly facing the medium (such as gas and ceramic wall), it simplifies to:
[0115]
[0116] As we will see later, specific combinations of surface finish, particle size, pore diameter, and bulk matrix porosity of the components of a tube bundle reactor can achieve unexpected improvements in heat exchange capabilities by radiation, especially at high temperatures in the range of 600°C to 1800°C.
[0117] In the context of the present invention, with respect to a mixture of alumina-zirconia metal oxides (ZTA), the following are therefore defined:
[0118] - A surface is considered ground or polished when its surface roughness is in the range of 0.01 μm to 1 μm;
[0119] - A surface is considered to have a rough finish when its surface roughness is in the range of 10 μm to 250 μm;
[0120] - When the average grain diameter (grain diameter, or particle diameter or crystal diameter) of the bulk structure is greater than 2μm, it is considered coarse-grained
[0121] - When the average particle size of the bulk structure is less than 2 μm, it is considered fine-grained
[0122] - When the average particle size of the bulk structure is greater than 0.2 μm, it is considered to have large diameter pores
[0123] - When the average particle size of the bulk structure is less than 0.2 μm, it is considered to have small diameter pores
[0124] - When the porosity of the bulk structure is greater than 0.5%, it is considered to be in high porosity
[0125] - When the porosity of the bulk structure is less than 0.5%, it is considered to be in low porosity
[0126] Based on what has been disclosed so far and taking into account the properties experimentally obtained for alumina-zirconia (ZTA) used to realize the reactor, some useful characteristics can be identified to construct a tube bundle reactor for high temperatures, the purpose of which is to:
[0127] · maximize heat transfer between the circulating heat transfer fluid on the shell side and the circulating fluid on the tube side;
[0128] Maximize heat transfer between the outer wall of the tube side and the inner wall of the tube side;
[0129] Maximize heat transfer between the inner wall of the tube and the reaction fluid circulating inside it;
[0130] Minimize heat transfer between the circulating heat transfer fluid on the shell side and the inner wall of the shell side;
[0131] Minimize heat transfer between the inner wall of the shell side and the outer wall of the shell side;
[0132] • Minimize the heat transfer between the outer wall of the shell side and the insulation material outside the reactor.
[0133] Consider the following facts:
[0134] - characteristics distinguishing the radiative properties of the medium and the properties of the surface treatment of the translucent medium have been defined;
[0135] - the properties of the fluids involved in the reaction have been defined;
[0136] -The fluid involved in the reaction acts as a "participating medium";
[0137] - Due to isotropy, the inner wall of the tube side is at the same temperature;
[0138] - For convective transport of the heat transfer fluid, the outer wall on the tube side is at substantially the same temperature as the inner wall on the shell side;
[0139] Desirable properties of alumina-zirconia (ZTA) materials for the tube side of a tube bundle reactor are:
[0140] - The inner and outer walls of the tube have high emissivity, which means high emissivity values on the tube side for relation (3), therefore:
[0141] o The surface of the tube is as mirror-like as possible and has a high roughness, so it has a rough finish
[0142] - The bulk structure of the tube side (in order to maximize emissivity) is fine-grained (small average particle size), with a small average pore diameter and high porosity
[0143] - According to relation (1), the bulk structure on the tube side has a low linear attenuation coefficient, so:
[0144] o The bulk structure of the tube side is coarse-grained (large average particle size), with large pore diameters and low porosity
[0145] In contrast, the behavior of the bulk structure on the tube side appears to depend on whether one moves toward maximizing the emissivity or toward decreasing the linear attenuation coefficient. rad The increase in the value of , the benefit of the bulk structure on the tube side is only modest in terms of the emissivity properties of the body itself compared to the advantage obtained from (1). Therefore, it is preferred to choose a tube side in the body structure configuration that is compatible with the reduction of the linear attenuation coefficient, i.e.: coarse grains (large average particle size), large pore diameter and low porosity.
[0146] Similar to what has been defined for the tube side of a shell and tube reactor, the desired properties of the alumina-zirconia (ZTA) material on the shell side of the reactor are:
[0147] - The inner and outer walls of the shell have low emissivity, which means that for (3) a low emissivity value of the shell, therefore:
[0148] oThe surface of the shell is ground (polished) and made as mirror-like as possible
[0149] - The bulk structure on the shell side (to minimize emissivity) is coarse-grained (large average particle size), with large average pore diameter and low porosity
[0150] - The main structure on the shell side has a high linear attenuation coefficient for (1), so:
[0151] o The bulk structure of the shell side is fine-grained (small average particle size), with a small average pore diameter and high porosity
[0152] The shell side is also the same as the tube side. In contrast, the behavior of the bulk structure appears to depend on whether to move in the direction of minimizing the emissivity or in the direction of increasing the linear attenuation coefficient. However, regarding the Λ of the bulk conductivity when radiating rad The reduction in the value, the benefit of the body structure related to the reduction in emissivity due to the body alone is moderate compared to the advantage obtained from (1). Therefore, even in this case, it is preferred to select a body structure configuration on the shell side that is compatible with an increase in the linear attenuation coefficient, i.e. fine particles (small average particle size), with a small average pore diameter and a high porosity.
[0153] By way of example of the combined advantages obtainable from the construction of a tubular reactor having the characteristics indicated above, the gap between the shell side and the tube side of the reactor was modeled with the aid of the HITRAN commercial software package to calculate the absorption coefficient of the heat transfer fluid (HTF). For the purposes of this modeling, it was assumed that the heat transfer fluid (HTF) was superheated steam at a temperature of 1300K and 10 bar, and that the material was 80 / 20 alumina-zirconia.
[0154] refer to Figure 7 , it is obvious that the heat transfer fluid (HTF) behaves as a participating thick medium, since its transparency (in many regions of the spectrum of interest) is exhausted after a few centimeters of penetration. Moreover, as is known from the literature, the emissivity of water vapor at about 1200 K and 10 bar is in the range of 0.12 to 0.15. Under these conditions, the evaluation using relation (3), considering two cylinders of equal radius "inside" and "outside" (inside is water vapor and outside is the ZTA alumina-zirconia shell), allows to define the sensitivity of the heat transfer by radiation to the type of surface treatment on the shell side. In particular, the emissivity of alumina-zirconia (ZTA) varies from 0.49 (surface with ground finish) to 0.51 (surface with rough finish). Therefore, using relation (3), a reduction of the heat transferred to the shell side by the gas equal to 1% is obtained.
[0155] Similarly, the refractory insulation mounted on the outside of the shell side of the reactor has an emissivity in the range of 0.65 to 0.9, with higher values being achieved with refractory / insulating materials designed to have high emissivity. Thus, with (3), a reduction in heat transfer from the shell side to the external insulation in the range of 3% to 4% is achieved with a surface having a ground finish of alumina-zirconia ZTA.
[0156] Using the same evaluation method as for the tube side, and considering that for the tube side the transfer of heat from the heat transfer fluid (HTF) must be maximized, an improvement of about 1% was obtained using the roughened polished surface.
[0157] As for the interior of the tube, assuming that the fluid circulating inside it is, for example, a mixture of CH4+CO2+H2O, the emissivity of this mixture at the temperature and pressure considered (1300 K, 10 bar) is approximately equal to the emissivity of superheated water vapor, i.e. about 0.1. Moreover, depending on the diameter of the tube, the circulating fluid (such as a mixture of CH4+CO2+H2O) may be thick or thin, in the latter case the improvement is negligible (substantially transparent fluid). According to literature data, if the diameter of the tube is less than 2 cm, the absorption coefficient is such that the mixture of the mentioned gases (CH4+CO2+H2O) is opaque to radiation; therefore, the improvement obtained with the treatment indicated for the inner surface of the tube is about 1%.
[0158] Further improvements in the efficiency of the radiative heat exchange inside the tubular reactor are obtained by using specific bulk properties of the alumina-zirconia matrix (particle size, porosity and pore diameter); these affect the linear scattering coefficient of the material, manifested by different diffuse reflectances (see Figure 3 ), as has been shown above. In fact, the linear scattering coefficient is directly related to the linear attenuation coefficient by means of relation (1) and acts inversely proportional to the radiation transmission. From experimental tests on alumina-zirconia (ZTA) (see Figure 3 ), a value of 0.80 was obtained for the coarse-grained alumina-zirconia and a value of approximately 0.82 was obtained for the fine-grained alumina-zirconia. An evaluation carried out with these values allowed an efficiency improvement of approximately 2.5% to be determined both on the shell side and on the tube side.
[0159] Taking into account all the contributions listed so far, the overall improvement in the efficiency of heat transfer by radiation achieved in a tubular reactor by utilizing the above-mentioned properties is about 11-12%.
[0160] This type of solution allows a more favorable thermal balance under operating conditions, with economic advantages and lower operating management costs quantifiable within the same percentage range identified for the overall improvement in exchange efficiency, based on values experimentally determined with samples of alumina-zirconia (ZTA) manufactured and tested in the laboratory.
[0161] Due to reasons related to technical and cost difficulties in obtaining alumina-zirconia samples, the tests and experiments discussed above were conducted using 80 / 20 alumina-zirconia samples. This definition is generally recognized and known in the art and generally refers to the amount of alumina and zirconia present in percentages in a mixture of metal oxides of the defined material. Therefore, although direct experiments were conducted using 80 / 20 alumina-zirconia samples, it is reasonable to expect that other mixtures of alumina-zirconia metal oxides (ZTA) will also have similar behavior with respect to heat transfer characteristics by radiation.
[0162] Considering the above disclosure, therefore, according to Figure 1 The present invention relates to a shell and tube reactor 1 suitable for use at temperatures ranging from 600° C. to 1800° C., comprising a plurality of tubes 21 and a shell 10 for heat exchange between a first heat transfer fluid circulating on the shell side and a second fluid circulating on the tube side, the reactor being characterized in that:
[0163] - The construction material is a mixture of aluminum oxide and zirconium oxide ZTA metal oxides;
[0164] - the outer surface of the housing side has a surface roughness in the range of 0.01 μm to 1 μm;
[0165] - the inner surface of the housing side has a surface roughness in the range of 0.01 μm to 1 μm;
[0166] The material on the housing side has an average particle size in the range from 0.15 μm to 10 μm, an average porosity in the range from 0.01% to 5% and an average pore diameter in the range from 10 nm to 0.2 μm.
[0167] In a preferred embodiment, as described above, the reactor 1 has the following characteristics:
[0168] - the outer surface of the housing side has a surface roughness in the range of 0.05 μm to 0.5 μm;
[0169] - the inner surface of the housing side has a surface roughness in the range of 0.05 μm to 0.5 μm;
[0170] The material on the housing side has an average particle size in the range from 0.3 μm to 5 μm, an average porosity in the range from 0.01% to 0.5% and an average pore diameter in the range from 50 nm to 0.1 μm.
[0171] The characterization and surface treatment of the bulk matrix of the material used for the shell side of the shell and tube reactor 1 improves the efficiency of the radiation contribution to the heat exchange between the heat transfer fluid (HTF) and the fluid circulating in the tubes 21 and minimizes heat losses to the external environment.
[0172] As expected, the combination of the specific characteristics of the material matrix and the surface finish of both the shell and tube sides 21 achieves additional unexpected advantages in terms of overall heat exchange efficiency within the reactor 1.
[0173] In another preferred embodiment of the present invention, as described above, the reactor 1 has the following characteristics:
[0174] - the outer surface of the tube 21 has a surface roughness ranging from 10 μm to 250 μm;
[0175] - the inner surface of the tube 21 has a surface roughness ranging from 10 μm to 250 μm;
[0176] The material on the tube side has an average grain size in the range of 0.01 μm to 0.5 μm, an average porosity in the range of 0.01% to 5% and an average pore diameter in the range of 0.1 μm to 10 μm.
[0177] In another preferred embodiment of the present invention, as described above, the reactor 1 has the following characteristics:
[0178] - the outer surface of the tube 21 has a surface roughness ranging from 40 μm to 120 μm;
[0179] - the inner surface of the tube 21 has a surface roughness ranging from 40 μm to 120 μm;
[0180] The tube-side material has an average particle size in the range of 0.05 μm to 0.25 μm, an average porosity in the range of 0.01% to 0.5% and an average pore diameter in the range of 0.2 μm to 2 μm.
[0181] In particular, the alumina-zirconia (ZTA) that can be used to construct the reactor 1 that is the subject of the present invention is a mixture of alumina-zirconia metal oxides in a weight percentage ranging from 95 / 5 to 70 / 30.
[0182] Therefore, in another preferred embodiment of the present invention, as described above, the construction material of the reactor 1 is a mixture of alumina-zirconia ZTA metal oxides in a weight percentage ranging from 95 / 5 to 70 / 30.
[0183] Taking into account the fact that the reactor 1 subject of the invention can be installed inside a concentrated solar power plant, using as heat transfer fluid (HTF) a fluid coming directly from heating by means of solar collectors, the temperature of the carrier fluid can reach extremely high values.
[0184] For these reasons, in another preferred embodiment of the present invention, as described above, the reactor 1 has a maximum design temperature in the range of 600°C to 1800°C.
[0185] It is known that materials comprising mixtures of metal oxides such as aluminium oxide and zirconium oxide, often also called ceramic materials, (obtained by sintering processes) exhibit mechanical strength and toughness characteristics that are generally unsatisfactory for industrial use or for obtaining complex artefacts. For these reasons, methods are known for toughening these materials with the aid of yttria or magnesium oxide. Toughened aluminium oxide-zirconia has mechanical strength and toughness that are significantly superior to the starting materials, and also allows machining with the aid of machine tools that is difficult to perform on the starting materials.
[0186] In another preferred embodiment of the invention, as described above, the material of the reactor 1 is toughened by means of yttrium oxide or magnesium oxide according to known techniques and methods.
[0187] In another preferred embodiment of the present invention, as mentioned above, the material of the reactor 1 is 80 / 20 alumina-zirconia toughened with the aid of yttria or magnesia according to known techniques and methods.
[0188] In a preferred embodiment of the present invention, as already described above, the mixture of alumina-zirconia metal oxides is toughened with yttria or magnesia such that the weight percentage of zirconia comprises yttria or magnesia in the range of 3 to 8 mole percent relative to the mole number of zirconia.
[0189] The shell and tube reactor 1 (inserted into an installation environment such as an installation of a concentrated solar field) utilizes a heat transfer fluid (HTF) from a parabolic mirror that moves at a pressure that can vary between 1 and 20 barg. For these reasons, in another preferred embodiment of the present invention, the reactor 1 has a shell side design pressure in the range of 1 to 20 barg, as described above.
[0190] In another preferred embodiment of the present invention, as described above, the reactor 1 has a tube side design pressure in the range of 1 to 20 barg.
[0191] The invention also relates to a redox method at high temperatures between 600°C and 1800°C, such as those involved in the synthesis of fuels and chemicals using solar energy. In particular, this method is suitable for partial or total decarbonization of all thermochemical production processes by using renewable energy sources, in order to reduce fossil emissions in the production process. These methods include synthesizing methanol from carbon dioxide and water (with or without methane), synthesizing hydrogen from water or via steam methane reforming (SMR), and synthesizing synthesis gas from carbon dioxide and water (with or without methane as a reagent). Another method in which high-temperature redox is envisaged is a method for producing methanol from methane / carbon dioxide / water or hydrogen from water / methane or using only water to produce hydrogen, after absorbing heat, the reduction step occurs spontaneously due to the action of thermal energy on the material. One of the greatest contributions to the greenhouse effect comes from carbon dioxide, and its significant increase in the atmosphere is the subject of mitigation actions at the international level. In order to try to manage and minimize the production of CO2 from human activities, in recent years, attempts have been made to use the same carbon dioxide where it is produced, avoiding sudden combustion in oil fields. In recent years, much effort has been devoted to developing methods for converting CO2 into other products or energy carriers (e.g. into methanol for use in motor vehicles or as a solvent or reagent). It should be remembered that methanol has a higher octane rating, burns more easily and has a higher latent heat of vaporization than gasoline. For these reasons, greater energy efficiency of the engine and reduction of gaseous emissions (HC, NO) can be obtained from the use of methanol. x) reduction. Unfortunately, the high thermodynamic stability of carbon dioxide requires high energy to convert it into other products. Chemical conversion to synthesis gas (a mixture of CO and H2) is one of the most studied ways to be able to produce methanol. Industrially, synthesis gas is synthesized mainly from fossil sources of natural gas or coal via steam reforming, combined steam reforming, catalytic and non-catalytic partial oxidation. In order to be able to produce synthesis gas from carbon dioxide, it is important to have abundant and cheap energy available to implement the endothermic reaction of CO2 valorization. If the renewable factor is added, then concentrated solar power will become the preferred option. From this point of view, a thermochemical conversion pathway of carbon dioxide and water based on metal oxides MO is being developed, which performs a two-stage redox cycle as shown in the following diagram:
[0192] Reduction: MOox→MOred+O2 (endothermic)
[0193] Oxidation: MOred+CO2→MOox+CO (exothermic)
[0194] MOred+H2O→MOox+H2 (exothermic)
[0195] Redox reactions include:
[0196] - Thermal reduction of metal oxides at high temperatures with release of oxygen
[0197] - Oxidation of the reduced metal by carbon dioxide and / or water or a mixture thereof at low temperature, resulting in the production of CO, hydrogen or synthesis gas.
[0198] In this way, by continuously implementing reduction and oxidation cycles, it is possible to produce synthesis gas for application purposes. One of the metal oxides studied is cerium (IV) oxide (CeO2), where the reduction occurs spontaneously at about 1300-1500 ° C, while the oxidation can occur at the same temperature or at a temperature of about 600-900 ° C. Usually, the reduction is carried out in a partial way to avoid the collapse of the oxide structure, resulting in the irreproducibility of the phenomenon. In fact, Ce (IV) does not change to the Ce (III) (Ce2O3) state, but a change is defined in terms of the stoichiometry of this oxide, δ is defined by:
[0199] CeO (2-δ) δ = [-(Δm x MW ceria) / (ms x MW oxygen)]
[0200] Where MW Ceria is the molecular weight of cerium dioxide, MW Oxygen is the molecular weight of oxygen, and ms is the mass of the test sample and Δm is its change in mass during reduction. In the redox cycle, the required energy can be provided by a concentrated solar field or another form of thermal renewable energy. A different approach is to use chemical reagents that facilitate the reduction of cerium oxide, thereby reducing the amount of energy involved, i.e., reducing it at temperatures below 1300°C (e.g., around 900-1200°C). The reduction in the energy specifications of this redox stage allows the use of solar fields with lower power and therefore with less initial and operating investment. Using temperatures below 1300°C also allows having less critical reaction systems, which has advantages from an implementation point of view.
[0201] As a reducing agent, methane can be used according to the following scheme, which is called a hybrid cycle:
[0202] MOox reduction: 3CH4+3 / 2O2→3CO+6H2
[0203] MOred oxidation: 2H2O+CO2 -3 / 2O2→CO+2H2
[0204] Overall reaction: 3CH4+2H2O+CO2→4CO+8H2
[0205] The oxygen involved in the reaction is the oxygen formally donated / taken by ceria in the redox cycle. In this way, 1 mole of CO2 is used together with 3 moles of CH4 and 2 moles of water to produce 4 moles of syngas, where the H2 / CO ratio is equal to 2. This ratio is the stoichiometric amount required for converting syngas to methanol:
[0206] 2H2+CO→CH3OH
[0207] The hybrid scheme produces 25% of the synthesis gas via carbon dioxide. Since the methane in the reforming is also burned to provide energy for the process, thereby producing CO2 at the same time, the hybrid cycle appears to be an environmentally friendly and renewable system in methanol production. Similar to what has been reported previously, the hybrid system can be used to produce hydrogen using only water in the oxidation step (with hydrogen formation) and adding another step to convert the CO produced from methane into another hydrogen via water gas shift.
[0208] The complete scheme for the redox production of hydrogen is as follows:
[0209] CH4+1 / 2O2<->2H2+CO CeO2 reduction
[0210] H2O+1 / 2O2<->H2 Cerium dioxide oxidation
[0211] CO+2H2O<->H 2+ CO2 Water Gas Shift
[0212] CH4+2H2O<->4H 2+ Final reaction of CO2
[0213] Alternatively, in the case of a redox material other than ceria or in the case of the same ceria but doped with a metal or surface modified, it can be assumed that the reduction reaction can take place at a T below 1300-1500°C and in any case above 600°C, whose redox cycle will be represented as follows:
[0214] MOox reduction: MOox + heat → MOred + 1 / 2O2
[0215] MOred oxidation: MOred + H2O → MOox + H2
[0216] Overall reaction: H2O → 1 / 2O2 + 8H2
[0217] In this case, no methane is used anymore, but only water as reagent.
[0218] The availability of a shell and tube reactor 1 as described above makes high temperature redox reactions possible by combining them with the use of renewable energy sources such as solar power generation.
[0219] Therefore, the present invention relates to a high temperature redox method, which comprises the following steps:
[0220] - providing a shell and tube reactor 1 according to any of the above preferred embodiments;
[0221] - circulating a first heat transfer fluid on the shell side of the shell and tube reactor 1, which heat transfer fluid has a temperature in the range of 600° C. to 1800° C. at the inlet of the reactor 1, the first heat transfer fluid comprising water or carbon dioxide or a mixture thereof;
[0222] - circulating a second fluid on the tube side of the shell and tube reactor 1;
[0223] - The redox reaction of the second fluid is initiated inside the shell-and-tube reactor 1 by the second fluid absorbing the heat released from the first heat transfer fluid.
[0224] In a preferred configuration of the described redox method, the second fluid comprises carbon dioxide and water or only water, optionally methane.
[0225] In a further preferred configuration of the described redox method, the second fluid comprises methane and water.
[0226] As mentioned above, the subject method of the present invention can utilize the presence of redox materials or even the catalyst to carry out the redox reaction.
[0227] In another preferred configuration, the above redox method comprises the step of providing a redox catalyst inside the tube bundle of the reactor 1. Such a catalyst for the redox reaction is preferably a metal oxide, and more preferably cerium oxide or a chemically or surface-modified form thereof.
[0228] The device of the invention thus conceived is in any case susceptible to numerous modifications and variations, all falling within the scope of the same inventive concept; moreover, all the details may be replaced by equivalent technical elements.
[0229] Therefore, the protection scope of the present invention is defined by the appended claims.
Claims
1. A shell and tube reactor 1 suitable for use at temperatures ranging from 600° C. to 1800° C., comprising a plurality of tubes (21) and a shell (10) for heat exchange between a first hot heat transfer fluid circulating on the shell side and a second fluid circulating on the tube side, the reactor being characterized in that: - The construction material is a mixture of aluminum oxide and zirconium oxide ZTA metal oxides; - the outer surface of the housing side has a surface roughness in the range of 0.01 μm to 1 μm; - the inner surface of the housing side has a surface roughness in the range of 0.01 μm to 1 μm; The housing-side material has an average particle size in the range of 0.15 μm to 10 μm, an average porosity in the range of 0.01% to 5% and an average pore diameter in the range of 10 nm to 0.2 μm.
2. The shell and tube reactor 1 according to claim 1, wherein: - the outer surface of the housing side has a surface roughness in the range of 0.05 μm to 0.5 μm; - the inner surface of the housing side has a surface roughness in the range of 0.05 μm to 0.5 μm; The housing-side material has an average grain size in the range from 0.3 μm to 5 μm, an average porosity in the range from 0.01% to 0.5% and an average pore diameter in the range from 50 nm to 0.1 μm.
3. The shell and tube reactor 1 according to any one of the preceding claims, wherein: - the outer surface of the tube (21) has a surface roughness ranging from 10 μm to 250 μm; - the inner surface of the tube (21) has a surface roughness ranging from 10 μm to 250 μm; The tube-side material has an average grain size in the range of 0.01 μm to 0.5 μm, an average porosity in the range of 0.01% to 5% and an average pore diameter in the range of 0.1 μm to 10 μm.
4. The shell and tube reactor 1 according to claim 3, wherein: - the outer surface of the tube (21) has a surface roughness ranging from 40 μm to 120 μm; - the inner surface of the tube (21) has a surface roughness ranging from 40 μm to 120 μm; The tube-side material has an average grain size in the range of 0.05 μm to 0.25 μm, an average porosity in the range of 0.01% to 0.5% and an average pore diameter in the range of 0.2 μm to 2 μm.
5. Shell and tube reactor 1 according to any of the preceding claims, wherein the construction material is a mixture of alumina-zirconia ZTA metal oxides in a weight percentage range of 95 / 5 to 70 / 30.
6. The shell and tube reactor 1 according to any one of claims 1 to 4, wherein the ZTA alumina-zirconia metal oxide mixture is toughened with yttria or magnesium oxide.
7. The shell and tube reactor 1 according to claim 6, wherein the construction material is a mixture of alumina-zirconia ZTA metal oxides in a weight percentage range of 95 / 5 to 70 / 30, toughened with yttria or magnesia, such that the weight percentage of zirconia includes yttria or magnesia in a range of 3 mol% to 8 mol% relative to the moles of zirconia.
8. The shell and tube reactor 1 of claim 7, wherein the construction material is an 80 / 20 mixture of alumina-zirconia ZTA metal oxides toughened with yttria or magnesia such that the weight percentage of zirconia includes yttria or magnesia in the range of 3 mol% to 8 mol% relative to the moles of zirconia.
9. Shell and tube reactor 1 according to any of the preceding claims, wherein the design pressure on the shell side is in the range of 1 to 20 barg.
10. Shell and tube reactor 1 according to any of the preceding claims, the reactor (1) having a tube bundle (20), wherein the design pressure on the tube side is in the range of 1 to 20 barg.
11. A high temperature redox method comprising the following steps: - providing a shell and tube reactor (1) according to any one of the preceding claims 1 to 10; - circulating a first hot heat transfer fluid on the shell side of the shell and tube reactor, the first heat transfer fluid having a temperature in the range of 600° C. to 1500° C. at the inlet of the reactor (1), the first heat transfer fluid comprising water or carbon dioxide or a mixture thereof; - circulating a second fluid on the tube side of the shell and tube reactor; - starting a redox reaction of the second fluid inside the tubes of the shell-and-tube reactor via absorption by the second fluid of heat released from the first hot heat transfer fluid.
12. A redox method according to claim 11, wherein the second fluid comprises carbon dioxide and water or only water, and optionally methane.
13. The redox method of claim 11, wherein the second fluid comprises methane and water.
14. The redox method according to any one of claims 11 to 13, comprising the step of providing a redox catalyst inside the shell and tube reactor (1).
15. The redox method according to claim 14, wherein the redox catalyst is a metal oxide.
16. The redox method according to claim 15, wherein the redox catalyst is cerium oxide.
Citation Information
Patent Citations
Rapid solar-thermal conversion of biomass to syngas
CN101522862A
Composite cavity type solar absorber
CN105066479A
ZTA ceramic material preparation method and material prepared from method
CN110015889A
Oxygen distribution reactor for liquid fuel combustion applicable of fuel reformer in a submarine
KR102228295B1
Solar thermochemical reactor and methods of manufacture and use thereof
US20170304794A1